Synthesis and anticancer activity of new carbohydrazide derivatives bearing furan moiety - TOK, Fatih; TİLKİ, Elif KAYA; DİKMEN, Miriş; KAYMAKÇIOĞLU, Bedia KOÇYİĞİT (Journal of Research in Pharmacy, 2022)
In this study, some new carbohydrazide derivatives bearing furan moiety were synthesized. All carbohydrazide structures have been characterized by IR, 1H-NMR and elemental analysis. Anticancer activity of compounds were investigated on A549 human lung cancer and BJ normal fibroblast cells. According to the MTT assay results, all compounds demonstrated the cytotoxic activity on A549 cells with IC50 values of 43.38-342.63 μM except compound 3g. Only the IC50 values of compound 3c was below 400 μM on BJ cells. Especially, compound 3e showed significant anticancer effects on A549 cells with IC50 value of 43.38 μM and also didn’t show cytotoxic effects on normal BJ cells.